A study of calf independence and social interaction of a captive killer whale (Orcinus orca) as a model for zoological research - Levy, Ally (Scholarly Repository, 2017)
Little is known about killer whale mother-calf interactions and alloparenting in the wild or in captivity. Studies of other marine mammals indicate that calves become more independent over time as their interactions with their mothers decrease and time spent with other individuals increases. The purpose of this study was two-fold. First, the goal was to contribute to improved monitoring of a killer whale calf post-parturition by systematically recording and scoring videos. The second goal was to better understand killer whale calf social development and independence, with implications for the conservation and management of wild populations. Video data were collected in situ, including 15-minute recordings of the calf daily for the first three months of life, until expiration. The videos were then coded and analyzed to determine the frequency and duration of time the calf was independent from her mother and/or interacting with her siblings. Results indicated that both independence and sibling interactions significantly changed over the three-month period. However, they did not follow the trend reported by previous research, in which calf development showed a positive correlation with age. In this project, the calf did show an increase in independence and sibling interaction between the first and second months, but both significantly declined in month three. It is possible that the decrease in calf independence was due to the declining health of the calf in month three, in which she expired 17 days into the month. This research can be added to previous data gathered on calf development. Zoological facilities allow for systematic data collection data that is nearly impossible to gather in the wild, which was exemplified by this study. Future studies on alloparenting and calf-adult interactions should be performed using orcas from another pod at a zoological facility.